2020
DOI: 10.3390/nu12102958
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glyceraldehyde-Derived Advanced Glycation End Products on β-Tubulin-Inhibited Neurite Outgrowth in SH-SY5Y Human Neuroblastoma Cells

Abstract: Nutritional factors can affect the risk of developing neurological disorders and their rate of progression. In particular, abnormalities of carbohydrate metabolism in diabetes mellitus patients lead to an increased risk of neurological disorders such as Alzheimer’s disease (AD). In this study, we investigated the relationship between nervous system disorder and the pathogenesis of AD by exposing SH-SY5Y neuroblastoma cells to glyceraldehyde (GA). We previously reported that GA-derived toxic advanced glycation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Previous studies on AGEs reported that the effects of AGEs were associated with their extracellular binding to RAGE or accumulation in numerous tissues; however, further research on these molecules is needed to clarify the impact of the intracellular generation of TAGE. The in vitro intracellular TAGE molecules that participate in cytotoxic effects in neuroblastoma cells [ 24 , 25 ], hepatocytes [ 26 , 27 , 28 ], pancreatic cells [ 29 ], cardiomyocytes [ 30 ], and myoblast cells [ 31 ] have been identified. These molecules are produced as intermediates during abnormal glucose and fructose metabolism in the presence of excess GA. TAGE appear to play roles in apoptotic/necrotic events, and thus, have been implicated in cell death and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on AGEs reported that the effects of AGEs were associated with their extracellular binding to RAGE or accumulation in numerous tissues; however, further research on these molecules is needed to clarify the impact of the intracellular generation of TAGE. The in vitro intracellular TAGE molecules that participate in cytotoxic effects in neuroblastoma cells [ 24 , 25 ], hepatocytes [ 26 , 27 , 28 ], pancreatic cells [ 29 ], cardiomyocytes [ 30 ], and myoblast cells [ 31 ] have been identified. These molecules are produced as intermediates during abnormal glucose and fructose metabolism in the presence of excess GA. TAGE appear to play roles in apoptotic/necrotic events, and thus, have been implicated in cell death and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated target proteins for TAGE using two-dimensional gel electrophoresis and mass spectrometry, and the findings obtained demonstrated that β-tubulin was one of the targets of TAGE. The formation of TAGE-β-tubulin, the abnormal aggregation of β-tubulin, and the inhibition of neurite outgrowth were observed in GA-treated SH-SY5Y cells [ 25 ]. These findings implicated the formation of TAGE-β-tubulin in the generation of PHF, a component of NFT.…”
Section: Cytotoxicity Of Tage In the Brainmentioning
confidence: 99%
See 3 more Smart Citations